The Alans in Mongolia and China: the main written sources (1253–1811) - Kaziev E.V. (Золотоордынское обозрение)
This paper is a source study review aimed at presenting the main information that details the history of the Alans’ service to the Mongols in Mongolia and China. The materials for the study were multilingual written sources covering the period from the mid-13th to the early 19th centuries. A tidy, single summarizing of information from sources on this issue, having such a wide chronological range, is the scientific novelty of the present study. The relevance of the study is determined by the absence of such a work in the existing scientific tradition. Based on the results of the review, a general conclusion was made that the Alans who served the Mongols in Mongolia and China took part in many significant foreign and domestic political events in Mongolian history that took place in the East Asia region from the mid-13th century onward, beginning with the conquest of Southern China which was complete in 1279 and ending with the internal political struggle in the Mongolian lands that followed the overthrow of the Yuan Dynasty in China in 1368. In addition, it is noted that one of the Alan leaders, Arugtai, was even able to unite the warring eastern Mongolian peoples for some time in the first quarter of the 15th century. At the same time, it is indicated that the Alans, who by the will of historical fate found themselves in Mongolia and China, could not avoid assimilation by the Mongols, having become part of this people, known as the Asuts. Nevertheless, it is argued that even after becoming part of the Mongolian people, the Alans continued to preserve such an important elements of their ethnic identity as their self-designation until the beginning of the 19th century.